Akt and STAT5 mediate naïve human CD4+ T-cell early metabolic response to TCR stimulation - Finlay, David; Jones, Nicholas; Vincent, Emma E.; Cronin, James G.; Panetti, Silvia; Chambers, Megan; Holm, Sean R.; Owens, Sian E.; Francis, Nigel J.; Thornton, Catherine A. (My University, 2019)
Metabolic pathways that regulate T-cell function show promise as therapeutic targets in diverse diseases. Here, we show that at rest cultured human effector memory and central memory CD4+ T-cells have elevated levels of glycolysis and oxidative phosphorylation (OXPHOS), in comparison to naïve T-cells. Despite having low resting metabolic rates, naive T-cells respond to TCR stimulation with robust and rapid increases in glycolysis and OXPHOS. This early metabolic switch requires Akt activity to support increased rates of glycolysis and STAT5 activity for amino acid biosynthesis and TCA cycle anaplerosis. Importantly, both STAT5 inhibition and disruption of TCA cycle anaplerosis are associated with reduced IL-2 production, demonstrating the functional importance of this early metabolic program. Our results define STAT5 as a key node in modulating the early metabolic program following activation in naive CD4+ T-cells and in turn provide greater understanding of how cellular metabolism shapes T-cell responses.
PUBLISHED
Keywords: Regulate T-cell function; T-cell; Cellular metabolism; Immunology, Inflammation & Infection; HUMAN T-CELLS; Immunometabolism